Analisis Buku Materi Ajar Bahasa Arab Kelas VIII MTs Darul Ihya Bogor - Shofiatul Fuadah; Dina Khaerunnisa; Fadhilah Luthfiyah Zain; Ubaidillah Ubaidillah (Jurnal Ilmiah Literasi Indonesia, 2025)
of ensuring alignment of content with the curriculum and its effectiveness in supporting the achievement of student competencies. The main objective of this study is to assess the feasibility of textbooks based on the structure, completeness, and integration of the material. This research was conducted through literature review and content analysis methods. Literature review is utilized to understand the standards of Arabic teaching materials, while content analysis is focused on analyzing the content of textbooks as the main object of study. The findings show that some parts of the book have not fully met the curriculum standards and are still weak in integrating language skills. The conclusion of this study states the need for improvement and development of textbooks to be more optimal in supporting Arabic language learning, and suggests the use of books that combine communicative and contextual approaches